DI TENGAH GELOMBANG INFLASI INFORMASI: MENIMBANG KEMBALI PENGGUNAAN SUMBER-SUMBER DIGITAL DALAM PENULISAN SEJARAH - Willy Alfarius (Puteri Hijau : Jurnal Pendidikan Sejarah, 2026)
In the last two decades of the 21st century, the production and supply of information and news has become increasingly massive after the internet became extremely accessible and usable. As a primary source for historical writing, the availability of news has significantly increased compared to the previous era, when it was initially limited to printed media such as newspapers and, to a lesser extent, television and radio. The emergence of social media, particularly in the mid-2000s, further exacerbated information inflation, as it made it easier for anyone to produce and distribute information, both written and visual. This article attempts to describe how the chaotic availability of information, which has reached a level never imagined before, especially by the great Indonesian historians of the 20th century, must be handled and addressed by historians today, and in the foreseeable future. Conflicts have often arisen between those who outright reject available digital sources of information and those who rely entirely on these non-conventional sources. Mapping and responding to these issues are necessary because existing information will continue to increase and become more decentralized, while at the same time, information production by established institutions is decreasing. Keywords: Digital Sources, Historical Research, Digital History Methodology.